1994
DOI: 10.1111/j.1445-2197.1994.tb02056.x
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐operative Anticoagulant Effects of Heparinization for Carotid Endarterectomy

Abstract: The question of whether or not to reverse heparin following carotid endarterectomy is a topic of debate. The potential reduction of the risk of thrombosis at the endarterectomy site with non‐reversal has to be measured against a potential increase in the risk of wound haematoma. This study prospectively followed activated clotting time (ACT) of 42 consecutive patients undergoing carotid endarterectomy. A standard heparin dose of 100 units/kg was used, and heparin reversal was employed only if the wound appeare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…ACT monitoring has been shown to be simple and inexpensive and to correlate reliably with both serum heparin concentration and partial thromboplastin time (11,15). Furthermore, several studies have suggested that the ACT value is more effective than partial thromboplastin time for monitoring the level of intraoperative anticoagulation (9,22). Nonetheless, whereas therapeutic ACT values have been established for cardiac surgery, appropriate anticoagulation for patients undergoing carotid endarterectomy (CEA) is not entirely clear (2,21).…”
mentioning
confidence: 99%
“…ACT monitoring has been shown to be simple and inexpensive and to correlate reliably with both serum heparin concentration and partial thromboplastin time (11,15). Furthermore, several studies have suggested that the ACT value is more effective than partial thromboplastin time for monitoring the level of intraoperative anticoagulation (9,22). Nonetheless, whereas therapeutic ACT values have been established for cardiac surgery, appropriate anticoagulation for patients undergoing carotid endarterectomy (CEA) is not entirely clear (2,21).…”
mentioning
confidence: 99%
“…It is also not clear which dose is optimal because 70 up to 100 IU/kg are used. 22,23 Most important, for these regimens, antagonization with protamine was recommended, which is a potential cause for significant morbidity. 24 In this respect, however, UFH is superior to LMWH because the at least partial inability to reverse the effect of enoxaparin is frequently regarded as a serious limitation for its use in vascular surgery.…”
Section: Discussionmentioning
confidence: 99%
“…23,25e28,36 High ACTs after heparin administration seem to be associated with haematoma formation. 24 In contrast, heparin reversal could increase the risk of periprocedural and immediate post-procedural thrombus formation. 26,27 The number of haemorrhagic and thromboembolic complications in all studies was too small to allow a comparison between the heparin and no heparin reversal groups.…”
Section: Discussionmentioning
confidence: 99%